Accuracy of the Wells Clinical Prediction Rule for Pulmonary Embolism in Older Ambulatory Adults. Issue 11 (3rd November 2014) - Schouten, Henrike J.; Geersing, Geert‐Jan; Oudega, Ruud; van Delden, Johannes J.M.; Moons, Karel G.M.; Koek, Huiberdina L.
<x xml:space="preserve">Abstract</x> Objectives To determine whether the Wells clinical prediction rule for pulmonary embolism (PE), which produces a point score based on clinical features and the likelihood of diagnoses other than PE, combined with normal D‐dimer testing can be used to exclude PE in older unhospitalized adults. Design Prospective cohort study. Setting Primary care and nursing homes. Participants Older adults (≥60) clinically suspected of having a PE (N = 294, mean age 76, 44% residing in a nursing home). Measurements The presence of PE was confirmed using a composite reference standard including computed tomography and 3‐month follow‐up. The proportion of individuals with an unlikely risk of PE was calculated according to the Wells rule (≤4 points) plus a normal qualitative point‐of‐care D‐dimer test (efficiency) and the presence of symptomatic PE during 3 months of follow‐up within these patients (failure rate). Results Pulmonary embolism occurred in 83 participants (28%). Eighty‐five participants had an unlikely risk according to the Wells rule and a normal D‐dimer test (efficiency 29%), five of whom experienced a nonfatal PE during 3 months of follow‐up (failure rate = 5.9%, 95% confidence interval (CI) = 2.5–13%). According to a refitted diagnostic strategy for older adults, 69 had a low risk of PE (24%), two of whom had PE (failure rate = 2.9%, 95% CI = 0.8–10%). Conclusion The use of the well‐known and widely used Wells rule (original or refitted) does not guarantee safe exclusion of PE in older unhospitalized adults with suspected PE. This may lead to discussion among professionals as to whether the original or revised Wells rule is useful for elderly outpatients.